Time Pressure and Health-Related Loss of Productivity in University Students: The Mediating Role of Exhaustion - Gusy, Burkhard; Lesener, Tino; Wolter, Christine (Frontiers in Public Health, 2021)
Introduction: The Study Demands-Resources (SD-R) framework is an influential theoretical basis to examine salutogenic and pathogenic effects of the study context on students’ health and well-being. Its health impairment process implies that study demands – the »bad things« at university – increase the risk of burnout and lead to negative outcomes such as health complaints, a loss of productivity, or even dropout. However, this assumption has not been validated longitudinally, yet. Methods: To examine the health impairment process properly, we conducted a longitudinal study with three occasions. We surveyed 392 students in three waves over a time lag of one year. We included time pressure as the major study demand, burnout as a mediator and health-related loss of productivity as the major outcome. We performed structural equation modelling to examine the assumptions proposed by the SD-R framework. Results: In line with our assumptions, time pressure predicted burnout which, in turn, predicted health-related loss of productivity in the long run. Hence – as assumed by the SD-R framework – burnout serves as a mediator between study demands and negative outcomes such as a loss of productivity. Discussion: Our study is the first that confirms SD-R’s health impairment process longitudinally. Since we know that time pressure serves as a major antecedent for burnout and even productivity loss, we are well-advised to establish appropriate interventions to reduce students’ time pressure.